Multilingual Semantic Web Services - Hallot, Frédéric (On the Move to Meaningful Internet Systems 2005: OTM 2005 Workshops, 2005)
In this paper, an overview of the PhD thesis with the same name will be presented. After an introduction of the subject and aim of the thesis, a couple of research questions will be asked. A brief overview of the state of the art in the domain will be done and then some problems that arise with it will be considered. Although the monolingual problematic is quite general and recurrent in most ontologies design tools, this thesis will focus on the approach used in DOGMA Studio. Some new terms and acronyms will be introduced : ”onternationalization”, ”concepton” and IMMO. Finally, some work issues for the thesis will be sketched then some conclusions will come before ending this document with some considerations about further problems that will follow the research.